Metallized polypropylene film and preparation process thereof

By introducing graphene/silver composite materials into polypropylene films, the high temperature and self-healing properties are improved by using sulfide bonds and disulfide bond functional group modifiers, the problem of aging of polypropylene films at high temperatures is solved, and the introduction is significantly improved Electrical strength and self-healing efficiency extend the life of the capacitor.

CN119219950APending Publication Date: 2024-12-31TONGLING HONGYU ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421440.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The polypropylene film aging at high temperatures leads to increased conductivity loss, reduced discharge efficiency and energy storage, poor self-healing performance, affecting the long-term reliability and life of metallized film capacitors.

Method used

Graphene is modified by surface modifiers containing sulfide-ether bond functional groups and disulfide bond functional groups, graphene/silver composite materials are prepared through silver-sulfur coordination, and polypropylene composite dielectric film is prepared by combining polypropylene resin. The film with excellent high temperature resistance and self-healing properties were prepared by melt blending and hot pressing film formation.

Benefits of technology

It significantly improves the dielectric strength and self-healing efficiency of the polypropylene composite dielectric film, enhances high temperature stability and self-healing performance, and extends the service life of the metallized film capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219950A_ABST
    Figure CN119219950A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric film research and development, and discloses a metallized polypropylene film and a preparation process thereof, and the preparation process comprises the following steps: preparing a surface modifier containing a thioether bond functional group and / or a disulfide bond functional group; the preparation method comprises the following steps: carrying out surface modification treatment on hydroxylated graphene by using a surface modifier, then mixing nano-silver powder with graphene of which the surface is modified with a thioether bond functional group and / or a disulfide bond functional group, and loading silver on the graphene through a silver-sulfur coordination effect to prepare the graphene / silver composite material. The graphene / silver composite material is used as a modifier to be introduced into polypropylene resin, and a melt blending and hot-pressing film forming method is adopted to prepare the polypropylene composite dielectric film. The polypropylene composite dielectric film developed by the invention not only has relatively excellent high temperature resistance, but also has relatively excellent high-temperature stability, the self-healing performance is also greatly improved, and the polypropylene composite dielectric film can be used for manufacturing a metallized film capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric film research and development, in particular to a metallized polypropylene film and a preparation process thereof. Background Art

[0002] Power electronic systems are mainly composed of power semiconductors, capacitors, gate drivers, inductors and resistors, among which capacitors account for about 20% of the total system. Their main functions are AC and DC filtering and energy storage. Metallized film capacitors account for 50% of the capacitor usage due to their high operating voltage, low dielectric loss, light weight and good self-healing performance. At present, the dielectric film used in metallized film capacitors is mainly polypropylene film. The maximum short-term operating temperature of polypropylene film is <105℃, and the long-term operating temperature is ≤85℃. The combined action of electric field and thermal field will accelerate the aging of polypropylene dielectric. When the temperature is higher than 85℃, the conductivity loss of polypropylene film increases, and the discharge efficiency and energy storage decrease.

[0003] In addition, self-healing is an important characteristic of metallized film capacitors. It is a complex process involving physical and chemical changes. Self-healing performance is a key performance to ensure the long service life and remarkable reliability of metallized film capacitors. Summary of the invention

[0004] The present invention independently develops a polypropylene composite dielectric film which is resistant to high temperatures and has excellent self-healing properties. The polypropylene composite dielectric film can be used to manufacture metallized film capacitors.

[0005] A process for preparing a polypropylene composite dielectric film comprises the following steps:

[0006] Step 1: Prepare a surface modifier containing a thioether functional group and / or a disulfide functional group. The surface modifier is a coupling agent I containing a thioether functional group, and its chemical structure is:

[0007]

[0008] Step 2: Surface modification of hydroxylated graphene is performed using the surface modifier in step 1, and then nano silver powder is mixed with graphene whose surface is modified with sulfide bond functional groups and / or disulfide bond functional groups, and silver is loaded on the graphene through silver-sulfur coordination to prepare a graphene / silver composite material;

[0009] Step 3: Introducing the graphene / silver composite material as a modifier into the polypropylene resin, and preparing a polypropylene composite dielectric film by melt blending and hot pressing film forming methods;

[0010] Wherein, the mass ratio of polypropylene resin to graphene / silver composite material is 100:(0.1-3).

[0011] Preferably, the surface modifier is a coupling agent II containing a thioether bond functional group and a disulfide bond functional group, and its chemical structure is:

[0012]

[0013] Preferably, the surface modifier is a coupling agent II containing a thioether functional group and a disulfide functional group and a cross-linking agent containing a thioether functional group and a disulfide functional group;

[0014] The chemical structural formula of the cross-linking agent is:

[0015]

[0016] Preferably, the coupling agent I is prepared by a method of catalyzing a nucleophilic addition reaction between the alkenyl functional group of allyl methyl sulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane using an alkaline substance.

[0017] Preferably, the coupling agent II is prepared by a method of catalyzing a nucleophilic addition reaction between the alkenyl functional group of allyl methyl disulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane using an alkaline substance.

[0018] Preferably, the cross-linking agent is prepared by a method of: using an alkaline substance to catalyze a nucleophilic addition reaction between the alkenyl functional group of diallyl disulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane.

[0019] Preferably, the alkaline substance catalyst is one of sodium hydroxide, sodium carbonate and sodium ethoxide.

[0020] The dielectric strength of a polypropylene composite dielectric film prepared according to the process is 500-700 V / μm and the self-healing efficiency is 45-75%.

[0021] The polypropylene composite dielectric film prepared according to the above process is used in the manufacture of metallized film capacitors.

[0022] Beneficial effects:

[0023] The present invention independently develops and synthesizes sulfur-containing coupling agent I, sulfur-containing coupling agent II and sulfur-containing cross-linking agent with self-healing performance based on molecular design mechanism, and uses sulfur-containing coupling agent and / or sulfur-containing cross-linking agent to compound graphene and silver nanoparticles to obtain graphene / silver composite material; and uses graphene / silver composite material as a modifier to modify polypropylene resin to obtain polypropylene composite dielectric film;

[0024] The experimental results show that compared with polypropylene film, the polypropylene composite dielectric film not only has excellent high temperature resistance, but also has excellent high temperature stability, and its self-healing performance has also been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the chemical reaction formula of sulfur-containing coupling agent I;

[0026] Figure 2 is the chemical structural formula of sulfur-containing coupling agent II;

[0027] Figure 3 is the chemical structural formula of the sulfur-containing cross-linking agent;

[0028] Figure 4 These are the performance experimental results of polypropylene composite dielectric films. DETAILED DESCRIPTION

[0029] The present invention combines graphene and silver nanoparticles by chemical bonding through a newly developed sulfur-containing coupling agent and / or sulfur-containing crosslinking agent to prepare a graphene / silver composite material, and utilizes the graphene / silver composite material to improve the dielectric properties, high temperature resistance and self-healing properties of a polypropylene film.

[0030] Experimental Example 1:

[0031] Synthesis of sulfur-containing coupling agent I: alkaline substances catalyze the nucleophilic addition reaction between the alkenyl functional group of allyl methyl sulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane to generate sulfur-containing coupling agent I. The chemical reaction formula is as follows: Figure 1 As shown;

[0032] The alkaline substance is one of sodium hydroxide, sodium carbonate and sodium ethoxide; sodium ethoxide is selected in this experimental example;

[0033] The specific experimental steps for synthesizing the sulfur-containing coupling agent I are as follows: 0.9 g of allyl methyl sulfide, 0.5 g of sodium ethoxide and 20 mL of anhydrous ethanol are added to a three-necked flask, stirred at room temperature until all dissolved, then 30 mL of 3-mercaptopropyltriethoxysilane solution (prepared with 2.4 g of 3-mercaptopropyltriethoxysilane and 30 mL of anhydrous ethanol) is added dropwise to the three-necked flask, the temperature is raised to 60° C. and stirred for reaction for 5 h, cooled to room temperature, washed with deionized water, dried over anhydrous magnesium sulfate, the solvent is removed by rotary evaporation, and vacuum dried to obtain the sulfur-containing coupling agent I;

[0034] The nuclear magnetic resonance hydrogen spectrum of sulfur-containing coupling agent I is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.63-0.67 (t, 2H), 1.20-1.24 (t, 9H), 1.65-1.70 (m, 2H), 2.07(s, 3H), 2.42-2.46(t, 2H), 2.71-2.80(m, 4H), 3.79-3.86(m, 6H).

[0035] Experimental Example 2:

[0036] Synthesis of sulfur-containing coupling agent II: alkaline substances catalyze the nucleophilic addition reaction between the alkenyl functional group of allyl methyl disulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane to generate sulfur-containing coupling agent II, whose chemical structure is as follows: Figure 2 As shown;

[0037] The alkaline substance is one of sodium hydroxide, sodium carbonate and sodium ethoxide; sodium ethoxide is selected in this experimental example;

[0038] The synthesis steps and reaction conditions of sulfur-containing coupling agent II are similar to those of sulfur-containing coupling agent I. The difference between sulfur-containing coupling agent II and sulfur-containing coupling agent I is that 0.9 g of allyl methyl sulfide is replaced by 1.2 g of allyl methyl disulfide.

[0039] The nuclear magnetic resonance hydrogen spectrum of sulfur-containing coupling agent II is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.61-0.65 (t, 2H), 1.20-1.24 (t, 9H), 1.64-1.71 (m, 2H), 2.32(s, 3H), 2.45-2.48(t, 2H), 2.76-2.89(m, 4H), 3.77-3.83(m, 6H).

[0040] Experimental Example 3:

[0041] Synthesis of sulfur-containing crosslinking agent: Alkaline substances catalyze the nucleophilic addition reaction between the alkenyl functional group of diallyl disulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane to generate a sulfur-containing crosslinking agent, the chemical structure of which is as follows: Figure 3 As shown;

[0042] The alkaline substance is one of sodium hydroxide, sodium carbonate and sodium ethoxide; sodium ethoxide is selected in this experimental example;

[0043] The sulfur-containing crosslinking agent was synthesized. The synthesis steps and reaction conditions thereof refer to the synthesis experiment of sulfur-containing coupling agent I. The difference between the synthesis experiment of sulfur-containing coupling agent I and the synthesis experiment of sulfur-containing coupling agent I is that 0.7 g of diallyl disulfide is used to replace 0.9 g of allyl methyl sulfide.

[0044] The H NMR spectrum of the sulfur-containing crosslinking agent is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.64-0.68 (t, 4H), 1.20-1.24 (t, 18H), 1.63-1.70 (m, 4H), 2.47-2.51 (t, 4H), 2.73-2.88 (m, 8H), 3.78-3.84 (m, 12H).

[0045] Experimental Example 4:

[0046] Preparation of hydroxylated nanographene: 20 g of graphene nanopowder and 200 mL of hydrogen peroxide aqueous solution (30 wt%) were added to a round-bottom flask, and the mixture was uniformly dispersed by ultrasonication for 10 min. The mixture was heated to 105 ° C and refluxed for 6 h under mechanical stirring. After cooling, the mixture was centrifuged at 5000 rpm for 5 min, and then washed with deionized water for 3 times. Finally, the mixture was freeze-dried for 9 h and vacuum-dried at 80 ° C for 5 h to obtain hydroxylated nanographene.

[0047] The graphene nanopowder is nanographite powder purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with the following specifications: average particle size 10 nm, average specific surface area 600 m 2 / g.

[0048] Embodiment 1:

[0049] Preparation of modified graphene I: using sulfur-containing coupling agent I to modify hydroxylated nanographene to obtain modified graphene I;

[0050] The specific experimental steps for preparing modified graphene I are as follows: add 2g of sulfur-containing coupling agent I, 20mL of methanol and 30mL of deionized water into a three-necked flask, add glacial acetic acid to adjust the pH to 4.5, heat to 50°C and stir to react for 2h, then continue to heat to 80°C under mechanical stirring, add 3g of hydroxylated nano-graphene into the three-necked flask and reflux to react for 3h, cool to room temperature, wash with methanol, precipitate, centrifuge, and dry to obtain modified graphene I.

[0051] Embodiment 2:

[0052] Preparation of modified graphene II: using sulfur-containing coupling agent II to modify hydroxylated nanographene to obtain modified graphene II;

[0053] The sulfur-containing coupling agent II was used to replace the sulfur-containing coupling agent I in Example 1, and the modified graphene II was prepared according to the same experimental steps and reaction conditions.

[0054] Embodiment three:

[0055] Preparation of modified graphene III: using sulfur-containing coupling agent II and sulfur-containing cross-linking agent to modify hydroxylated nanographene to obtain modified graphene III;

[0056] 1 g of sulfur-containing coupling agent II and 1 g of sulfur-containing cross-linking agent were used to replace 2 g of sulfur-containing coupling agent I in Example 1, and modified graphene III was prepared according to the same experimental steps and reaction conditions.

[0057] Embodiment 4:

[0058] Preparation of graphene / silver composite material I: Based on the silver-sulfur coordination effect, the modified graphene I is modified with silver nanoparticles to prepare the graphene / silver composite material I;

[0059] The specific experimental steps for preparing the graphene / silver composite material I are as follows: 5 g of modified graphene I and 1 g of nano-silver powder are added to 100 mL of methanol, ultrasonically dispersed for 30 min, heated to 50 ° C and stirred for 5 h, cooled to room temperature, washed with methanol, precipitated, centrifuged, and dried to obtain the graphene / silver composite material I;

[0060] Among them, nanosilver powder was purchased from Shanghai Chaowei Nanotechnology Co., Ltd., with the following specifications: average particle size 20nm, average specific surface area 42.0m 2 / g.

[0061] Embodiment five:

[0062] Modified graphene II and modified graphene III were used in turn to replace the modified graphene I in Example 4, and graphene / silver composite materials II and graphene / silver composite materials III were prepared respectively according to the same preparation steps and experimental conditions.

[0063] Embodiment six:

[0064] Preparation of polypropylene composite dielectric film I: 10 g of polypropylene resin and 0.25 g of graphene / silver composite material I were added to a Haake torque rheometer preheated to 100° C., melt-mixed for 20 min at a processing temperature of 180° C. and a rotation speed of 60 r / min, cut with a pelletizer to obtain 1-5 mm nano-composite polypropylene particles, and then hot-pressed by a hot press at 180° C. and 125 MPa, and bubbles were removed by a cycle for 5 times. The film was taken out after holding the pressure for 10 min to obtain a polypropylene composite dielectric film I with a thickness of 50 μm;

[0065] The polypropylene composite dielectric film can be used to prepare a metallized polypropylene film and a corresponding film capacitor. The preparation method comprises the following steps: subjecting the polypropylene composite dielectric film to metallized electrode evaporation to prepare a metallized polypropylene film, slitting the film into films of a predetermined width and then winding the film into a capacitor core, staggering the upper and lower edges to ensure that the metallized film is in contact with only one side surface; spraying gold on the two sides to form capacitor electrodes, and subjecting the capacitor core to performance improvement through heat treatment and empowerment; and then subjecting the film to welding, assembly, packaging and testing procedures to obtain a metallized polypropylene film capacitor.

[0066] The polypropylene resin was purchased from Beijing Yanshan Petrochemical Co., Ltd. of Sinopec Group, and its brand number is C1608.

[0067] Embodiment seven:

[0068] Graphene / silver composite material II and graphene / silver composite material III were used in turn to replace the graphene / silver composite material I in Example 6, and polypropylene composite dielectric film II and polypropylene composite dielectric film III were prepared respectively according to the same preparation steps and experimental conditions.

[0069] Comparative Example 1:

[0070] Preparation of polypropylene blended dielectric film: using 0.15 g of graphene nanopowder and 0.1 g of nanosilver powder to replace 0.25 g of graphene / silver composite material I in Example 6, and following the same preparation steps and experimental conditions, a polypropylene blended dielectric film was prepared;

[0071] The graphene nanopowder is the same as that in Experimental Example 4; and the nanosilver powder is the same as that in Example 4.

[0072] Comparative Example 2:

[0073] Preparation of polypropylene film: Compared with the polypropylene composite dielectric film I, the only difference is that the polypropylene film is prepared without using the graphene / silver composite material I.

[0074] Performance Test:

[0075] (1) Dielectric strength test: The breakdown voltage of polypropylene composite dielectric film samples at room temperature, 85°C, and 105°C was tested using a Chroma 19057 withstand voltage test analyzer at a voltage of 12 kV, a voltage rise rate of 200 V / s, and a voltage rise time of 60 s. The dielectric strength (V / μm) was calculated as breakdown voltage / thickness.

[0076] (2) Mechanical properties test: A 30 mm × 5 mm polypropylene composite dielectric film sample was fixed on a STX500 tensile testing machine and subjected to a tensile test at a tensile rate of 2 mm / min, and the initial tensile strength (MPa) was calculated as: maximum load / (width × thickness);

[0077] (3) Self-healing performance test: A 30 mm × 5 mm polypropylene composite dielectric film sample was cut into two sections with a blade, and the cuts were placed close together. The film was placed in a 60°C oven for self-healing for 3 h, and then fixed on a tensile testing machine for tensile testing. The tensile strength after self-healing (MPa) = maximum load / (width × thickness), and the self-healing efficiency (%) = tensile strength after self-healing / initial tensile strength were calculated.

[0078] The above experimental results are shown in Table 1 below;

[0079] Table 1 Performance experimental results of polypropylene composite dielectric film

[0080]

[0081] According to the dielectric strength experimental data in Table 1, Figure 4 ;

[0082] (4) Dielectric property test: The upper and lower surfaces of the film sample (a disc with a diameter of 15 mm) prepared by the present invention were plated with copper as electrodes using a DZ450 high vacuum resistance evaporation metal coating apparatus to obtain a dielectric film of a metallized capacitor. The dielectric film was measured at room temperature, 85°C, and 105°C using a DMS-1000 series high temperature dielectric impedance thermospectrometer at 10 4 Dielectric properties of dielectric films of metallized capacitors were tested at Hz;

[0083] The above experimental results are shown in Table 2 below.

[0084] Table 2 Performance test results of dielectric films of various metallized capacitors

[0085]

[0086]

[0087] By comprehensively analyzing the above experimental results, the following conclusions can be drawn:

[0088] (1) The polypropylene composite dielectric film obtained by modifying the polypropylene film with the three graphene / silver composite materials developed by the present invention has a beneficial technical effect of significantly improving the dielectric strength at high temperatures of 85°C and 105°C compared with the pure polypropylene film, and its mechanical properties and self-healing properties are also greatly improved;

[0089] (2) The three graphene / silver composite materials developed by the present invention are used to modify the polypropylene film and thus prepare the metallized capacitor. The dielectric constant of the polypropylene composite dielectric film of the metallized capacitor does not change much with temperature and the dielectric loss is less than 0.05, indicating that it has good high temperature stability.

Claims

1. A process for preparing a polypropylene composite dielectric film, characterized in that: The following steps are involved: Step 1: Prepare a surface modifier containing a thioether functional group and / or a disulfide functional group. The surface modifier is a coupling agent I containing a thioether functional group, and its chemical structure is: Step 2: Surface modification of hydroxylated graphene is performed using the surface modifier in step 1, and then nano silver powder is mixed with graphene whose surface is modified with sulfide bond functional groups and / or disulfide bond functional groups, and silver is loaded on the graphene through silver-sulfur coordination to prepare a graphene / silver composite material; Step 3: Introducing the graphene / silver composite material as a modifier into the polypropylene resin, and preparing a polypropylene composite dielectric film by melt blending and hot pressing film forming methods; Wherein, the mass ratio of polypropylene resin to graphene / silver composite material is 100:(0.1-3).

2. The process for preparing a polypropylene composite dielectric film according to claim 1, characterized in that: The surface modifier is a coupling agent II containing a thioether bond functional group and a disulfide bond functional group, and its chemical structure is:

3. The process for preparing a polypropylene composite dielectric film according to claim 2, characterized in that: The surface modifier also includes a cross-linking agent containing a thioether bond functional group and a disulfide bond functional group; The chemical structural formula of the cross-linking agent is:

4. The process for preparing a polypropylene composite dielectric film according to claim 1, characterized in that: The preparation method of the coupling agent I is as follows: alkaline substances catalyze the nucleophilic addition reaction between the alkenyl functional group of allyl methyl sulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane to obtain the coupling agent I.

5. The process for preparing a polypropylene composite dielectric film according to claim 2, characterized in that: The preparation method of the coupling agent II is as follows: alkaline substances catalyze the nucleophilic addition reaction between the alkenyl functional group of allyl methyl disulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane to obtain the coupling agent II.

6. The process for preparing a polypropylene composite dielectric film according to claim 3, characterized in that: The preparation method of the cross-linking agent is as follows: alkaline substances catalyze the nucleophilic addition reaction between the alkenyl functional group of diallyl disulfide and the mercapto functional group of 3-mercaptopropyltriethoxysilane to obtain the cross-linking agent.

7. A process for preparing a polypropylene composite dielectric film according to any one of claims 4 to 5, characterized in that: The alkaline substance catalyst is one of sodium hydroxide, sodium carbonate and sodium ethoxide.

8. A polypropylene composite dielectric film prepared by the process according to any one of claims 1 to 6, characterized in that: The dielectric strength of the polypropylene composite dielectric film is 500-700 V / μm, and the self-healing efficiency is 45-75%.

9. Use of a polypropylene composite dielectric film according to claim 8 in manufacturing metallized film capacitors.